Alterations of Lipid Metabolism in Cancer: Implications in Prognosis and Treatment - Fernández, Lara P.; Gómez de Cedrón, Marta; Ramírez de Molina, Ana (Frontiers in Oncology, 2020)
Cancer remains the second leading cause of mortality worldwide. In the course of this multistage and multifactorial disease, a set of alterations takes place, with genetic and environmental factors modulating tumorigenesis and disease progression. Metabolic alterations of tumors are well recognized and are considered as one of the hallmarks of cancer. Cancer cells adapt their metabolic competences in order to efficiently supply their novel demands of energy to sustain cell proliferation and metastasis. At the present time, there is a growing interest in understanding the metabolic switch that occurs during tumorogenesis. Together with the Warburg Effect and the increased glutaminolysis, lipid metabolism has emerged as essential for tumour development and progression. Indeed, several investigations have demonstrated the consequences of lipid metabolism alterations in cell migration, invasion and angiogenesis, three basic steps occurring during metastasis. In addition, obesity and associated metabolic alterations have been shown to augment the risk of cancer and to worsen its prognosis. Consequently, an extensive collection of tumorogenic steps have been shown to be modulated by lipid metabolism, affecting not only the growth of primary tumours, but mediating progression and metastasis. Besides, key enzymes involved in lipid-metabolic pathways have been associated with cancer survival and have been proposed as prognosis biomarkers of cancer. In this review, we will analyze the impact of obesity and related tumour microenviroment alterations as modifiable risk factors in cancer, focusing on the lipid alterations co-occurring during tumorigenesis. The value of precision technologies and its application to target lipid metabolism in cancer will also be discussed. The degree to which lipid alterations, together with current therapies and intake of specific dietary components, affect risk of cancer is now under investigation and innovative therapeutic or preventive applications must be explored.